Literatura infantil no Brasil: a voz da FNLIJ nas premiações de 2012 e 2013 - Juliana Valeria de Abreu (2015)
The present research, which is placed in the field of Education and Language, sought to explicate what is quality in childrens literature according to Fundação Nacional do Livro Infantil e Juvenil FNLIJ [ National Foundation of Childrens and Young Adult Book] taking as analysis corpus the justifications related to Prêmio FNLIJ 2012 Produção de 2011 e Prêmio FNLIJ 2013 Produção de 2012 [FNLIJ 2012 Awards 2011 Production and FNLIJ 2013 Awards 2012 Production], published by that institution. We carried an analysis of the discourse produced by the reader-voters and assumed by FNLIJ in the justifications for the awards, based on the categories which were children centered, as the presumed reader of the works, namely, The Best Book for Children, The Best Toy-Book, and The Best TranslationAdaptation for Children. We have contributions from Discourse Analysis DA, presented by Charaudeau, Maingueneau; bakhtinian concepts on language and discourse conceptions; the order of discourse according to Foucault; presuppositions of textual linguistics according to Costa Val, and the concepts of field and symbolic power according to Bourdieu. We have studied, in the justifications discourse, what FNLIJ highlights and values on the discourses produced by its readers-voters, which constitute its institutional voice. The diversity of voices adds to the discourse and to the award and establishes a dialogical relationship which is inherent to the institutions discourse. For analysis methodology, we used the presuppositions of Critical Discourse Analysis CDA, guided by the studies of Fairclough and its three-dimensional discourse conception, which considers the dimensions of text, discourse practice and social practice. The merits appointed in the winning literary works produce a discourse constituted by a scientific ethos and by the ethos of life world (Fairclough), approximating the justifications to the potential presumed readers on statute of the awards.